An update on prevention of malaria in travelers. (August 2021) - Agudelo Higuita, Nelson Iván; White, Bryan Pinckney; Franco-Paredes, Carlos; McGhee, Miranda Ann
Malaria, a parasitic disease caused by protozoa belonging to the genus Plasmodium, continues to represent a formidable public health challenge. Despite being a preventable disease, cases reported among travelers have continued to increase in recent decades. Protection of travelers against malaria, a potentially life-threatening disease, is of paramount importance, and it is therefore necessary for healthcare professionals to be up to date with the most recent recommendations. The present review provides an update of the existent measures for malaria prevention among travelers.